Chiral π-Conjugated Double Helical Aminyl Diradical with the Triplet Ground State - Guo, Haoxin; Rajca, Andrzej (Synlett, 2024)
We describe effective development of the highly diastereoselective synthesis of double helical tetraamine 2-H2-C2 and propose a mechanism for its formation. The resolution of 2-H2-C2 is facilitated by a high racemization barrier of 43 kcal mol–1 and it is implemented via either a chiral auxiliary or preparative supercritical fluid chromatography. This enables preparation of the first high-spin neutral diradical, with spin density delocalized within an enantiomeric double helical π-system. The presence of two effective 3-electron C–N bonds in the diradical leads to: (1) the triplet (S = 1) high-spin ground state with a singlet-triplet energy gap of 0.4 kcal mol–1 and (2) the long half-life of up to 6 days in 2-MeTHF at room temperature. The diradical possesses a racemization barrier of at least 26 kcal mol–1 in 2-MeTHF at 293 K and chiroptical properties, with an absorption anisotropy factor |g| ≈ 0.005 at 548 nm. These unique magnetic and optical properties of our diradical form the basis for the development of next-generation spintronic devices.1 Introduction2 Synthesis and Resolution of the C2-Symmetric Double Helical Tetraamine 2-H2-C23 Synthesis and Characterization of Neutral High-Spin Aminyl Diradical 22•-C24 Conclusion
Keywords: helical structures; radicals; chiral resolution; electrophilic aromatic substitution; electron transfer; oxidation; aminyl diradicals